The Influence of Work Discipline and Work Motivation on Employee Performance with Job Satisfaction as an Intervening Variable at PT. Indonesian Living Plank - Nurhidayah, Anugrah; Wahyu Pratiwi, Krisnandini (Universitas Mercu Buana, 2025)
This research aims to test and analyze the influence of work discipline and work motivation on performance with job satisfaction as an intervening variable at PT. Plank Living Indonesia. The population in this study was 79 employees. Research data was collected from the results of questionnaires to 79 respondents and then carried out statistical analysis. This approach uses a quantitative approach with statistical analysis techniques, namely partial least squares – structural equation model (PLSSEM) which aims to carry out path analysis with latent variables. The research results show that work discipline has a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Job satisfaction mediates the influence of work discipline on employee performance. Job satisfaction mediates the influence of work motivation on employee performance.